2009
DOI: 10.1243/09544100jaero542
|View full text |Cite
|
Sign up to set email alerts
|

Imperfection measures of eigen- and periodic modes of axially loaded stringer-stiffened cylindrical shell

Abstract: The influence of initial geometric imperfections in the shapes of eigenmodes and periodic modes on the load-carrying capacity of a steel stringer-stiffened cylindrical shell subject to axial compression is studied. For comparison of the influence of different shapes, the imperfections are normalized by an integral-energy measure, which is considered as an alternative to the commonly applied amplitude. The shell dimensions are chosen out of the set of 24 small-scale specimens tested between 1981 and 1984 at Imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…As it will be shown below an eigenmode of the channel possesses this kind of distortion. Another measure derives from the elastic strain energy hypothetically required to distort the originally perfect structural element into the considered imperfect shape [10][11][12]. Assuming a geometric imperfection w 0 , its energy measure EM (w 0 ) is defined as the square root of the elastic strain energy functional evaluated for w 0 .…”
Section: Eigenmode Analysis and Measures Of Geometric Imperfectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…As it will be shown below an eigenmode of the channel possesses this kind of distortion. Another measure derives from the elastic strain energy hypothetically required to distort the originally perfect structural element into the considered imperfect shape [10][11][12]. Assuming a geometric imperfection w 0 , its energy measure EM (w 0 ) is defined as the square root of the elastic strain energy functional evaluated for w 0 .…”
Section: Eigenmode Analysis and Measures Of Geometric Imperfectionsmentioning
confidence: 99%
“…(3). The hypothetic strain energy of a distorted shape can be directly obtained introducing the imperfection as imposed deformation in the linear elastic FEM model Sadovský et al [12]. Even incomplete deformation field can be introduced, e.g.…”
Section: Eigenmode Analysis and Measures Of Geometric Imperfectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these works it was confirmed that the statement that the simple prescription of the amplitude for the imperfection in the shape of the elastic buckling mode is not satisfactory for general applications. The maximum initial curvature as a measure of the hypothetic elastic strain energy governs [4]. The results were used in Czechoslovak Bridge Standard Č SN 73 6205 (1984), cl.…”
Section: Introductionmentioning
confidence: 99%
“…Stiffened panels are essential parts of aerospace structures due to their weight to stiffness ratio. For the safe design of new products it is important to investigate the loading response of these parts and to determine their failure load [1][2][3][4][5][6]. The outcome is crucial for virtual testing during the certification procedure.…”
Section: Introductionmentioning
confidence: 99%